Magnetised and unmagnetized axisymmetric particle-in-cell simulations of ion energy distributions in cathodic vacuum arcs. (1st August 2022) - Ryan, Alexander; Bilek, Marcela; Cairns, Iver H; McKenzie, David R
Abstract: Cathodic arcs are electrical discharges consisting of a succession of discrete pulses of energetic plasma travelling from the surface of a cathode toward an anode. Currently, there are no vacuum arc simulations where spots are continuously generated with a set frequency, including the far-field plasma jet, with the inclusion of kinetic behaviour for both ions and electrons. The VSim 11 particle-in-cell software was used to simulate specific vacuum arcs as axisymmetric, electrostatic, and fully kinetic, from the initial generation of each cathode spot to the streaming plasma discharge at a far field, validating the predictions against experimental data. The models were configured to match the experimental arc gun of Zohrer et al and the Mevva V experiment with the cathode materials Al and Nb. The ion and electron velocity data were collected at the far edge of the simulation domain, analogous to a physical energy detector. The simulations successfully predicted the evolution of ion charge state energy distributions, showing peak unmagnetized ion energies that agree with prior experimental data, resulting in a mean error of 3% for Al and Nb. A peak in the electrostatic potential is observed above the cathode surface, supporting the potential hump theory as the cause of the higher-than-expected ion energies observed in cathodic arc discharges. Lower than expected relative energies between ion charge states are observed, matching prior experimental results, with this coupling of ion charge states attributed to non-stationary electrostatic wave–particle interactions, as the use of collisionless simulations rules out Coulombic ion friction. Magnetised simulations incorporated a statically powered short solenoid equivalent to the coil used in the Mevva V experiment to create a diverging magnetic nozzle. The magnetised simulation results demonstrate an annular jet of magnetically confined plasma and indicate an increase in nonstationary electrostatic effects including wave–particle interactions.